Validity of the modified Conconi running test - Sentija, D.; Vucetic, V.; Markovic, G. (International Journal of Sports Medicine, 2007)
The aim of this study was to assess the validity of a fast ramp treadmill protocol for determination of the heart rate deflection point (HRdp) and speed of deflection (Sdp) in trained runners. Fifty-one trained male runners performed a standard (Tstand; speed increase 1 km · h-1 every 60 s) and a fast (Tfast; speed increase 1 km · h-1 every 30 s) incremental treadmill test until volitional exhaustion. Heart rate was continuously recorded, and the HRdp was estimated after data averaging as the point of deflection in the linear speed/HR relationship. The HRdp and Sdp recorded in Tfast were compared with the corresponding values obtained in Tstand by examining the Student's t-test, correlation coefficient (r), and limits of agreement (LoA). The HRdp recorded during standard and fast treadmill protocol were highly correlated (r = 0.92, p < 0.001) and similar to each other (p = 0.79). In contrast, Sdp was highly correlated (r = 0.91, p < 0.001), but increased significantly with the faster ramp function (p < 0.001). No evidence of systematic bias was evident in the HRdp (95 % LoA of 0.2 ± 7.3 bpm), while a uniform, systematic bias was evident for Sdp in the Tfast (95 % LoA of 1.6 ± 1.5 km · h-1). We conclude that a fast ramp treadmill protocol (speed increase 1 km · h-1 every 30 s) may be used for determination of the HRdp in trained runners, while Sdp is protocol dependent and caution is warranted regarding its practical applicability.